Parametric optimisation of friction welded 17-4 PH SS alloy using Taguchi techniques. (2018) - Mahendiran, S.; Ramanujam, R.; Mohanavel, V.; Ravikumar, M.M.; Madhan, G.; Vinothkumar, P.
Friction welding (FW) is a solid state technique used mostly for joining similar or dissimilar materials owing to batch production with less time consumption. In friction welding, the joints are formed in the solid state by utilising the heat generated by friction. The objectives of this project is to obtain friction weld element of 17-4 PH Stainless steel alloy (Grade 630) and optimising the friction welding parameters in order to establish the weld strength and its quality. In this research work, the experiment is undergone to examine the tensile strength of friction welding 17-4 PH Stainless steel alloy. The experiment is conducted by varying the input parameters like rotational speed, friction and forging force, friction and forging time using Taguchi's L9 orthogonal array. For each experiment tensile strength was examined and the optimum welding condition for maximising tensile strength was determined.